Sport-specific training targeting the proximal segments and throwing velocity in collegiate throwing athletes - Palmer, T.; Uhl, T. L.; Howell, D.; Hewett, T. E.; Viele, K.; Mattacola, C. G. (Journal of Athletic Training, 2015)
Context: The ability to generate, absorb, and transmit forces through the proximal segments of the pelvis, spine, and trunk has been proposed to influence sport performance, yet traditional training techniques targeting the proximal segments have had limited success improving sport-specific performance.